Pengaruh Diagram Vee pada Model Pembelajaran Team Assisted Individualization Terhadap Peningkatan Motivasi dan Hasil Belajar Siswa SMP (UPEJ Unnes Physics Education Journal, 2017)
Teacher centered learning method which teacher usually used for Science Learning made students bored and can not following learning process well so the learning outcomes decrease. To increase motivation and learning outcomes, teacher needs various learning models. One of the learning models that can be applied is Team Assisted Individualization with Vee Diagram. This study aims to determine the effect of Vee Diagram on the learning model of Team Assisted Individualization in improving student's motivation and learning outcomes. In this research the research design used was quasi experimental design with non-equivalent control group pretest-posttest with the sample chosen based on purposive sampling. Population of this study was students with eight grade of 8 Junior High School in Semarang. Sample of this study were A class as experiment class and B class as control class. Motivation and learning outcomes obtained from pretest and post test. Student learning outcomes have increased significantly marked by was . While learning motivation also made a significant increase marked with is . So it means motivation and learning outcomes of experiment class better than control class.